Blow-Up Results for a Nonlinear Hyperbolic Equation with Lewis Function. (11th October 2009) - Tahamtani, Faramarz
Abstract : The initial boundary value problem for a nonlinear hyperbolic equation with Lewis function in a bounded domain is considered. In this work, the main result is that the solution blows up in finite time if the initial data possesses suitable positive energy. Moreover, the estimates of the lifespan of solutions are also given.